Place of oligopeptide H-Met-Glu-His-Phe-Pro-Gly-Pro-OH in the therapy and rehabilitation of patients with ischemic stroke - Spirin, N N; Fedorov, V N; Vdovichenko, V P (Zhurnal nevrologii i psikhiatrii imeni S.S. Korsakova, 2024)
Cerebrovascular diseases (CVDs) are one of the leading causes of death and disability In Russia: they rank second in the structure of mortality from diseases of the circulatory system and in the overall mortality of the population. Successful treatment of CVD involves an integrated approach to the problem, taking into account the compensation of cardiovascular disorders, the elimination of neurological and psychopathological syndromes, the improvement of cerebral circulation and the use of neuroprotective agents that increase the resistance of brain tissue to hypoxia and ischemia. Insufficient clinical efficacy of neuroprotectors is due to a number of objective reasons, of which only two are universal. The first of these reasons is the timing of the start of therapy in the clinic, as a rule, is outside the «therapeutic window»; the second reason is the fact that disturbance of the patency of the cerebral vessels in the affected area makes it difficult or impossible to deliver the drug to the penumbra area. The way out of this situation is the intranasal route of drug administration, which is characteristic for the analogs of regulatory peptides such as for H-Met-Glu-His-Phe-Pro-Gly-Pro-OH (MGHPPGP). The review of clinical studies indicates that MGHPPGP is clinically effective in the treatment of ischemic stroke both in the acute period of stroke and in the recovery period. The clinical efficacy of MGHPPGP was shown both in atherothrombotic and cardioembolic subtypes of stroke, against the background of blood flow disturbances in both the carotid and vertebrobasilar systems.